Stabilisasi Tanah Lunak Menggunakan Geopolimer untuk Meningkatkan Nilai CBR Subgrade - Prasetyo, Querida Addisty; Firmansyah, Yerry Kahaditu; Farichah, Himatul (Universitas Nahdlatul Ulama Blitar, 2025)
Clay soil is a type of cohesive soil with low bearing strength, so it requires improvement through a stabilization process. The aim of this research is to identify changes in the physical and mechanical properties of soil with the addition of geopolymer composed of fly ash and alkali activator. The case study in this research is the Lamongan STA 1+270 northern ring road project. The geopolymer variation used consists of fly ash with percentages of 10%, 15% and 20%, with alkali activator sodium silicate (Na2SiO3) and sodium hydroxide (NaOH) 8M with a ratio of 1:1. The test method applied in this research involves testing physical and mechanical properties, including measuring water content, specific gravity, Atterberg limit, plasticity index, and California bearing ratio (CBR) in the laboratory. This research shows that the addition of 15% fly ash and alkali activator provides the most optimal CBR value of 8.23%, an increase from the original soil CBR value of 5.87%. This CBR value indicates that the addition of geopolymer to soft soil can improve the characteristics of the soil. This research concludes that the use of geopolymer can improve the quality of clay soil.